THE EXISTENCE OF GIRIK AS EVIDENCE OF OWNERSHIP BASED ON POSITIVE LAW IN INDONESIA - Endang Hadrian (Adisam Publisher, 2026)
Every individual has the right to have private property rights where these property rights cannot be taken arbitrarily by anyone. Looking at a historical overview before the UUPA was born, with regard to agrarian regulations in Indonesia there is still a dualism of regulations that apply. As we know, the term girik is often heard in the land sector. Girik is a letter for a land including related to land tenure from generation to generation or custom. Girik land is generally inherited or from his family. Thus it can be said that in general, girik land does not have an official certificate. Of course, the unofficial nature of the certificate will create the potential for problems to occur in the future. This research uses the type of research used is normative juridical. This research is a legal research conducted by examining literature which is referred to as secondary data. The formulation of the problem included in this research is related to how is the existence of girik certificates as proof of ownership of land based on agrarian law in Indonesia? and how to change the status of girik land into a certificate of ownership in Indonesia? So the results of the study stated that the UUPA does not recognize girik as proof of ownership of a land. This was confirmed in the Decision of the Supreme Court of the Republic of Indonesia. No. 34/K/Sip/1960, dated February 19, 1960, it was also emphasized that a petuk/girik letter was not proof of land rights. Just as a starting point.